Efektifitas Pemasaran UKM Berbasis Kayu Limbah: Studi Pada UKM Liidi Furniture Di Kecamatan Serpong, Kota Tangerang Selatan - Atin Yuliati; Siti Nur Malihatus; Tri Iis Wardani; Erika Sekar Sawitri; Siti Maryama (ITB Ahmad Dahlan Jakarta, 2018)
Marketing strategy is a very important thing for a company in which marketing strategy is a way of achieving the goal of a company, no exception, small and medium enterprises. This article reports the results of research marketing practices which is implemented by SMEs and studied their effectiveness. The elaboration of the results is discussed further in this article.